Powder co-injection moulding - Hanson, S. M. J. (Cranfield University, 2000)
A novel powder processing technique has been developed by combining conventional powder injection moulding with polymer co-injection moulding, to permit the in-situ surface engineering of metal or ceramic components as an integral step within the processing cycle. The new technique has been used to produce surface engineered iron based components with either corrosion resistant or wear resistant surfaces, and to produce alumina based components with toughened surfaces. The most critical factor for the feasibility of surface engineered components is that the sintering profiles of the skin and core materials must be well matched or differential shrinkage or delamination will result. A particular requirement of surface engineering is the ability to control the surface engineered skin profile. Polymer injection moulding modelling software was applied to predict the surface engineered skin profiles of the surface engineered metal/ceramic components. Successful skin profile prediction is dependent on the characterisation of the feedstock materials being injection moulded. Several feedstocks have been characterised for their material properties and first pass models developed to predict the feedstock material properties as a function of their individual material properties and mass or volume ratios. It has been demonstrated that the design of the feedstock composition and injection moulding process conditions can be optimised by the use of computer-based injection moulding modelling software to achieve the desired surface engineered skin profile. A methodology has been developed that outlines all the stages necessary for successful powder co-injection moulding.